Chronological innovations in biogas biodigesters design technology in Ethiopia - Miftah F. Kedir (Universitas Negeri Semarang, 2026)
Biodigester design of National Biogas Programme of Ethiopia (NBPE) was modified five times from the year 2009 to 2023. Three more design model biodigesters were introduced namely small and medium scale prefabricated plastic geomembrane and medium sized fixed dome biodigesters. The five biodigesters modified were SINIDU 2008, SINIDU 2010, Solid State Digester (SSD), Black Cotton Soil Digester (BCD) and MITIN 2012 (2.5m3). Simplicity during construction, affordability, environmental conditions and needs of users were the main benefits obtained in chronologically improved SINIDU biodigester models. In NBPE, the last modified biodigester used in all environmental conditions was SINIDU 2010 that replaced both SINIDU and SINIDU 2008. Modification of the design did not have considerable change on daily biogas production rate. For example, SINIDU, SINIDU 2008 and SINIDU 2010 produces 2m3, 1.75m3 and 1.75m3 biogas per day with 50kg of daily cow dung, respectively. Introduced alternative prefabricated design was suitable for the users and masons as the design is easy to install and adaptable to different environmental conditions. Introduction of solid baffle to SINIDU 2008 and its following version to get less volume of buffer resulted in less Hydraulic Retention Time (HRT) from 50 days in SINIDU model to 35 days in SINIDU 2008. Other design modification was for MITIN 2012 biodigester which the manhole is at the top of the dome and sealed but for other models it is through outlet chamber. The design for BCD is robust than other designs due to its spherical/oval shape but for SINIDU model and its version, the shape of the digester is cylindrical. Innovations such as SSD and injera mitad and stove were at pilot stage and not scaled up. Therefore, research institutes and universities should strengthen additional roles on further modification/development of injera mitad and stove to get easy access to market penetration.